Prarancangan Pabrik Magnesium Sulfat Dari Magnesium Karbonat Dan Asam Sulfat Kapasitas 40.000Ton/Tahun - Perdana, Sanjaya Putra, Rois Fatoni, S.T., M.Sc., Ph.D (2017)
Magnesium sulfate plant is needed in Indonesia because of increasing imports over the last few years. Magnesium sulfate is used in various industries, including textiles, plastics, fertilizers and pharmaceuticals. The reaction of magnesium carbonate and sulfuric acid occurs in the solid-liquid phase in the CSTR at a temperature of 82°C and atmospheric pressure that is exothermic, irreversible and isothermal. Requirement of raw material magnesium carbonate is 1,830.34kg/hr and sulfuric acid 2,123.99kg/hr produce magnesium sulfate heptahydrate 5,050.51kg/hr or 40,000tons/hr grading 99.5%. Requirement of process water is 21,594.62kg/hr and utilities water 12,274..04kg/hr, while for steams produced by the boiler is 473.83kg/hr. This plant requires electricity for 129.5KW provided by PLN and provided generator as a reserve. Compressed air needs of 34.52m3/hr. The factory is planned to set in Gresik, East Java in 2020 with a land area 21,580m2 with 190 employees. The factory is planned to operate for 330hari /year with a capital of Rp 355,544,651,898 and $27,012,965.50. Based the economic analysis obtained profit before tax amounting to Rp 81,130,501,461 per year, after taxes, the profits reached Rp 60,847,876,096 per year. Percent Return On Investment (ROI) before tax amounted to 22.82% and 17.11% after tax. Pay Out Time (POT) before tax is 3.05 years and 3.69 years after tax. Break Even Point (BEP) amounted to 56.12% and Shut Down Point (SDP) amounted to 27.27%. Investment Rate of Return (IRR) accounted for 36.45%. Based the data analysis of the feasibility of the above it can be concluded that the plant is profitable and feasible to set.